P356 A comparison of innovative strategies to promote engagement with an IBD patient portal. (27th May 2021) - Carlson, S; McCartney, S; Harrow, P
Abstract: Background: Patient portals are available on most major electronic health record (EHR) platforms and present many opportunities to improve patient engagement with services, the quality of data captured and therefore healthcare outcomes and patient satisfaction. Our centre looks after 5100 patients with IBD. We recently adopted the EPIC Systems patient portal MyChart which allows patients to view results, letters and complete patient reported outcomes (PRO). At baseline, few patients were registered for this platform. Our aim was to compare patient engagement with MyChart using a low and higher cost approach and to evaluate patient satisfaction with the platform. Methods: 160 consecutive patients were invited to join MyChart between September and October 2020. The low-intensity intervention group were invited to join MyChart via a standardised email without further communication. Newly registered patients and active patients were sent a portal message with disease-specific PRO questionnaire 7 days prior to clinic (HBI, SCCAI and IBD Control). Patients in the high-intensity intervention group received a telephone reminder to encourage completion at each step, which took on average 2 minutes, in addition to email. Engagement with the platform was measured prospectively. After clinic a patient-experience questionnaire was sent to all patients who signed up to the platform. Results: 72 patients were included in the low intensity group and 88 in the high intensity group. At baseline only 33% patients were already signed up to MyChart. Significantly more patients newly registered with the patient portal following the high intensity intervention compared to the low (75% vs. 30%, p <0.0001). Overall, patients in the high intensity group were significantly more likely to complete the PRO compared to the low (53% vs. 28%, p=0.002). Patients already registered were 5 times more likely to complete the PRO in the high intensity group compared to low (p=0.017). Platform engagement was not significantly impacted by gender or ethnicity. There was a trend toward lower engagement in patients over 65. 63 patients provided feedback. 87% found MyChart easy to use and 94% said they would complete the PRO questionnaires again. Conclusion: In our patient cohort, a higher intensity strategy significantly increased patient registration and engagement with a new patient portal at a minimal cost of time and resource. Healthcare providers can facilitate patient engagement with patient portals and overcome barriers to adoption to unlock transformative opportunities for better quality IBD care, disease monitoring and population-based research.